Chapter and Verse: From Variety to Uniformity in Scholarly Source Citation Practice - Lusinchi, Dominic (KULA)

(untitled) (University of Victoria Libraries, 2026)
Being provided with the source of a scholarly product (book, data, document, etc.) used in a published work is an important aspect of communication in the scholarly world because it allows the author’s peers to verify the results presented therein. Until recently, inconsistency, idiosyncratic practices, and a lack of explicit standards have been the dominant characteristics of the history of supplying bibliographic information for a publication mentioned. This essay uses Robert K. Merton’s (1910–2003) well-known paper “Science and the Social Order” (1938) as a case study to illustrate how “deficient” bibliographic referencing hampers the research process. The long-standing absence of norms regulating source referencing information was gradually reversed during the twentieth century, when sets of formalized and standardized rules were put into place and codified as the new millennium approached–especially with the advent of digital technology. This article examines the variegated ways in which bibliographic material was provided (or not) and suggests how a convergence of factors put an end to this “disorderly” bibliographic sourcing environment.